Misleading indicators [ how to reliably measure your business - Green, Philip , 1959-; Gabor, George (Santa Barbara, California : Praeger, 2012)
This book reveals the hidden and potentially misleading nature of measurements, empowering readers to avoid making critical business decisions that are harmful, unreasonable, unwarranted, or plain wrong.
1. What indicators indicate -- 2. Counting, recounting, and miscounting -- 3. Measuring accurately with instruments -- 4. Rating, scoring, and ranking reliably -- 5. How people react to measurements -- 6. Why performance dashboards mislead -- 7. Focusing employees with measurements -- 8. Going against the flow : navigating changing data streams -- 9. How averages distort indicators -- 10. Opposing views : are you being misled? -- 11. Misleading ourselves with measurements of risk
Includes bibliographical references (p. [269]-274) and index
Keywords: Economic indicators; Management -- Statistical methods; Performance -- Statistical methods; Work measurement